Prediction of In Vivo Knee Mechanics During Daily Activities Based on a Musculoskeletal Model Incorporated with a Subject-Specific Knee Joint - Li Zhang; Hui Li; Xianjie Wan; Peng Xu; Aibin Zhu; Pingping Wei (Bioengineering)
The objective of this study was to develop a musculoskeletal model incorporated with a subject-specific knee joint to predict the tibiofemoral contact force (TFCF) during daily motions. For this purpose, 18 healthy participants were recruited to perform the motion data acquisition using synchronized motion capture and force platform systems, and motion simulation based on an improved musculoskeletal model for five daily activities, including normal walking, stair ascent, stair descent, sit-to-stand, and stand-to-sit. The proposed musculoskeletal model included subject-specific models of bones, cartilages, and meniscus, detailed knee ligaments and muscles, deformable elastic contacts, and multiple degrees of freedom (DOFs) of the knee joint. The prediction accuracy was demonstrated by the good agreements of TFCF curves between the model predictions and in vivo measurements for the five activities (RMSE: 0.216~0.311 BW, R2: 0.928~0.992, and CE: 0.048~0.141). Based on the validated model, the TFCF on total, medial, and lateral compartments (TFCFTotal, TFCFMedial, and TFCFLateral) during the five daily activities were predicted. For TFCFTotal, the peak force for stair descent or sit-to-stand was the largest, followed by stair ascent or stand-to-sit, and finally normal walking. For TFCFMedial, stair descent had the largest peak, followed by stair ascent. There were no significant differences between the peak TFCFMedial values of normal walking, sit-to-stand, and stand-to-sit. For TFCFLateral, the peak of sit-to-stand was the largest, followed by stand-to-sit or stair descent, and finally normal walking or stair ascent. This study is valuable for further understanding the biomechanics of a healthy knee joint and providing theoretical guidance for the treatment of knee osteoarthritis (KOA).